A two-dimensional in situ fatigue cohesive zone model for crack propagation in composites under cyclic loading. (January 2016) - Nojavan, S.; Schesser, D.; Yang, Q.D.
Highlights: Formulate, implement, and validate a new non-Paris-Law-based fatigue CZM. Provide an efficient cycle jump strategy for high-cycle fatigue simulation. Demonstrate the fatigue CZM can be calibrated from simple fatigue fracture tests. Demonstrate the fatigue CZM can predict mixed-mode fatigue crack propagation. Abstract: In this paper a two-dimensional fatigue cohesive zone model (CZM) for crack propagation in composites under cyclic loading has been formulated and validated through successful predictions of fatigue crack growth under pure and mixed mode conditions for several different composites. The proposed fatigue CZM assumes simple power-law functions for fatigue damage accumulation of which the damage parameters can be calibrated from simple fatigue tests under pure mode I and mode II conditions. The model relies solely on the in situ cohesive responses for fatigue damage rate calculation, enabling the differentiation of the local elemental load history from the global load history. An effective cycle jump strategy for high-cycle fatigue has also been proposed. It has been demonstrated that once calibrated, the fatigue CZM can predict the Paris laws for the pure modes. Furthermore, it can predict the Paris laws of any mixed-mode conditions without the need of additional empirical parameters. This is of significant practical importance because it leads to greatly reduced experimental needs for mixed mode crack propagation widely observed in composites under cyclic loads.